Ferrite compositions, electronic components, and power supplies

JP2026165927APending Publication Date: 2026-10-14TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058588
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0007】 近年、PoC(Power over Coaxial)向けインダクタ要求が増えており、さらなる性能改善が求められている。とりわけ、従来よりも高い電流(たとえば2~3A)でインダクタンスや透磁率が低下しない材料の要求が増えている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165927000001_ABST
    Figure 2026165927000001_ABST
Patent Text Reader

Abstract

To provide a ferrite composition that can improve DC superposition characteristics through a different approach than conventional methods, and electronic components and power supply devices using the same. [Solution] The ferrite composition contains 39.0 to 43.0 mol% Fe2O3, 5.50 to 9.50 mol% CuO, 24.0 to 28.0 mol% ZnO, and the remainder as nickel oxide. Per 100 parts by weight of the main component, the minor components contain 0.05 to 0.50 parts by weight of Bi2O3, 2.3 to 3.3 parts by weight of SiO2, and 0.05 parts by weight or less (including 0) of CoO.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a ferrite composition, an electronic component, and a power supply device.

Background Art

[0002] Conventionally, as shown in, for example, the following Patent Document 1, material development for improving Bs (saturation magnetic flux density) has been carried out in order to improve the direct current superposition characteristics of ferrite compositions.

[0003] For this purpose, composition development has been conducted for iron oxides in ferrite compositions around the stoichiometric composition (50 mol%), but there was a limit to increasing Bs by this method.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

Problem to be Solved by the Invention

[0005] An exemplary object of the present invention is to provide a ferrite composition capable of improving direct current superposition characteristics by an approach different from conventional ones, and an electronic component and a power supply device using the same.

Means for Solving the Problem

[0006] To achieve the above object, a ferrite composition according to one aspect of the present invention is A ferrite composition having a main component and a subcomponent, The main component is 39.0 to 43.0 mol% of iron oxide in terms of Fe2O3, 5.50 to 9.50 mol% of copper oxide in terms of CuO, 24.0 to 28.0 mol% of zinc oxide in terms of ZnO, The remainder contains nickel oxide, With respect to 100 parts by weight of the main component, the minor component is: Bismuth oxide, 0.05 to 0.50 parts by weight in terms of Bi2O3, Silicon oxide in SiO2 equivalent amounts: 2.3 to 3.3 parts by weight. Contains cobalt oxide in an amount of 0.05 parts by weight or less (including 0) in terms of CoO.

[0007] In recent years, there has been an increasing demand for inductors for Power over Coaxial (PoC) applications, requiring further performance improvements. In particular, there is a growing need for materials that do not experience a decrease in inductance or permeability at higher currents (e.g., 2-3A) than conventional materials.

[0008] Conventional ferrite compositions have had difficulty meeting such requirements. However, according to one aspect of the present invention described above, it is possible to provide a ferrite composition with excellent DC superposition characteristics, in which the inductance and permeability do not decrease easily at high currents of 2A to 3A or higher than conventional ferrite compositions, and electronic components having this composition.

[0009] A core or electronic component according to one aspect of the present invention comprises the above-mentioned ferrite composition.

[0010] A power supply device according to one aspect of the present invention includes the above-mentioned ferrite composition. [Brief explanation of the drawing]

[0011] [Figure 1] Figure 1 shows a core containing a ferrite composition according to one embodiment of the present invention. [Figure 2] Figure 2 is a cross-sectional SEM image of the core shown in Figure 1. [Figure 3] Figure 3 is a graph showing the change in magnetic permeability with respect to electric current for ferrite compositions according to the embodiment and comparative example of the present invention. [Modes for carrying out the invention]

[0012] The embodiments will be described below.

[0013] In addition to the toroidal type shown in Figure 1, the core (magnetic core) shape of the coil-type electronic component according to this embodiment can be exemplified by FT type, ET type, EI type, UU type, EE type, EER type, UI type, drum type, pot type, cup type, etc. A desired coil-type electronic component can be obtained by winding one or more wires around this core. The ferrite core 2 according to this embodiment shown in Figure 1 is made of the ferrite composition according to this embodiment.

[0014] The ferrite composition according to this embodiment is a Ni-Cu-Zn ferrite, and contains iron oxide, copper oxide, zinc oxide, and nickel oxide as its main components.

[0015] In 100 mol% of the main component, the iron oxide content is 39.0 to 43.0 mol% in terms of Fe2O3, preferably 40.0 to 42.0 mol%, 40.1 to 41.9 mol%, or 40.8 to 41.4 mol%. If the iron oxide content is too low, the initial permeability tends to decrease. If the iron oxide content is too high, the DC superposition characteristics deteriorate, and the rate of decrease in permeability and inductance tends to increase (the change becomes larger) at high currents.

[0016] Of the 100 mol% of the main component, the copper oxide content is 5.50 to 9.50 mol% in terms of CuO, preferably 6.50 to 8.50 mol% or 7.05 to 7.65 mol%. If the copper oxide content is too low, the initial permeability tends to decrease. If the copper oxide content is too high, the DC superposition characteristics deteriorate, and the rate of decrease in permeability and inductance tends to increase (the change becomes larger) at high currents.

[0017] In 100 mol% of the main components, the content of zinc oxide is 24.0 to 28.0 mol%, preferably 25.0 to 27.0 mol% or 25.6 to 26.2 mol% in terms of ZnO. If the content of zinc oxide is too low, the initial magnetic permeability tends to decrease. If the content of zinc oxide is too high, the DC superposition characteristics deteriorate, and the rate of decrease in magnetic permeability and inductance at high current tends to increase (the change becomes larger).

[0018] The balance of the main components may consist solely of nickel oxide.

[0019] The ferrite composition according to the present embodiment contains, in addition to the above main components, bismuth oxide, silicon oxide and cobalt oxide as auxiliary components.

[0020] The content of bismuth oxide is 0.05 to 0.55 parts by weight, preferably 0.15 to 0.45 parts by weight in terms of Bi₂O₃, relative to 100 parts by weight of the main components. If the content of bismuth oxide is too low, the DC superposition characteristics deteriorate, and the rate of decrease in magnetic permeability and inductance at high current increases (the change becomes larger). If the content of bismuth oxide is too high, the initial magnetic permeability tends to decrease.

[0021] The content of silicon oxide is 2.3 to 3.3 parts by weight, preferably 2.5 to 3.1 parts by weight in terms of SiO₂, relative to 100 parts by weight of the main components. If the content of silicon oxide is too low, the DC superposition characteristics deteriorate, and the rate of decrease in magnetic permeability and inductance at high current increases (the change becomes larger). If the content of silicon oxide is too high, the initial magnetic permeability tends to decrease.

[0022] The content of cobalt oxide is 0.05 parts by weight or less (including 0), preferably 0.02 parts by weight or less (including 0) in terms of CoO, relative to 100 parts by weight of the main components, and it is more preferable that cobalt oxide is not substantially contained. If the content of cobalt oxide is too high, the initial magnetic permeability tends to decrease.

[0023] In addition, the ferrite composition according to this embodiment may contain other minor components. Examples of other minor components that may be included in the ferrite composition according to this embodiment include oxides such as magnesium oxide, manganese oxide, tungsten oxide, molybdenum oxide, and zirconium oxide, and may be included in an amount of 0.10 parts by weight or less per 100 parts by weight of the main component, but it is preferable that they are not included at an impurity level or higher.

[0024] Furthermore, the ferrite composition according to this embodiment may also contain oxides of unavoidable impurity elements in the raw materials in amounts ranging from several ppm to several hundred ppm. Specific examples of unavoidable impurity elements include typical metal elements such as B, C, S, Cl, Se, Br, Te, I, Li, Na, Mg, Al, K, Ga, Ge, Sr, In, Sn, Sb, Ba, Pb, and Bi, as well as transition metal elements such as Sc, Ti, V, Cr, Y, Nb, Pd, Ag, Cd, Hf, and Ta.

[0025] Figure 2 shows an example of a cross-sectional photograph of a ferrite core 2 made of the ferrite composition according to this embodiment. In the ferrite composition according to this embodiment, by using the composition described above, a segregated phase 2a of a composite oxide (ZnSiO3) containing Zn and Si can be observed in cross-sectional observation of the composition.

[0026] The size of the segregated phase 2a is not particularly limited, but is, for example, about the same as or less than the equivalent circular diameter of the ferrite particles, specifically, about 2 to 10 μm in equivalent circular diameter. The area ratio of the segregated phase 2a in the cross-section of the ferrite composition (cross-sectional size in which 100 or more ferrite particles are observed) is not particularly limited, but is preferably 5 to 20%.

[0027] In the ferrite composition according to this embodiment, as shown by the solid line in Figure 3, for example, even when the DC current (horizontal axis in Figure 3) becomes 2A to 3A or higher, the rate of decrease in magnetic permeability is small (rate of change on the vertical axis in Figure 3), and the DC superposition characteristics are significantly improved compared to the conventional example shown by the dotted line. The reason for this is not entirely clear, but it is thought that, for example, the segregation phase 2a (see Figure 2) made of ZnSiO3 may be influencing it as a microgap or the like.

[0028] Next, an example of a method for producing the ferrite composition according to this embodiment will be described.

[0029] First, the starting materials (the main component and the secondary component) are weighed and mixed to obtain a raw material mixture. Mixing methods include, for example, wet mixing using a ball mill or dry mixing using a dry mixer. It is preferable to use starting materials with an average particle size of 0.1 to 3 μm.

[0030] As the main raw materials, iron oxide (α-Fe2O3), copper oxide (CuO), zinc oxide (ZnO), nickel oxide (NiO), or composite oxides can be used. Furthermore, various compounds that become the above-mentioned oxides or composite oxides upon firing can also be used. Examples of substances that become the above-mentioned oxides upon firing include elemental metals, carbonates, oxalates, nitrates, hydroxides, halides, organometallic compounds, and the like.

[0031] Tribismuth oxide (Bi2O3), silicon oxide (SiO2), and cobalt oxide (CoO) can be used as raw materials for the secondary components. The same procedures as for the main component raw materials should be followed.

[0032] Next, the raw material mixture is calcined to obtain calcined material. Calcination is performed to convert the raw material mixture into a form suitable for subsequent processes by causing thermal decomposition of the raw materials, homogenization of the components, formation of ferrite, disappearance of ultrafine powder through sintering, and grain growth to an appropriate particle size. Such calcination is preferably carried out at a temperature of 800 to 1100°C for about 1 to 3 hours. Calcination may be carried out in the atmosphere (air), or in an atmosphere with a higher oxygen partial pressure than the atmosphere or in a pure oxygen atmosphere. The mixing of the main component raw material and the secondary component raw material may be carried out before or after calcination.

[0033] Next, the calcined material is pulverized to obtain pulverized material. Pulverization is performed to break down the agglomeration of the calcined material and obtain a powder with appropriate sinterability. If the calcined material forms large lumps, coarse pulverization is performed first, followed by wet pulverization using a ball mill or attritor. Wet pulverization is performed until the average particle size of the calcined material is preferably about 1 to 2 μm.

[0034] Next, the crushed material is granulated to obtain granulated material. Granulation is performed to convert the crushed material into aggregated particles of an appropriate size, into a form suitable for molding. Examples of such granulation methods include pressure granulation and spray drying. In the spray drying method, a commonly used binder such as polyvinyl alcohol is added to the crushed material, which is then atomized in a spray dryer and dried at a low temperature.

[0035] Next, the granules are molded into a predetermined shape to obtain a molded body. Examples of granule molding methods include dry molding, wet molding, and extrusion molding. Dry molding is a molding method in which the granules are filled into a mold and compressed (pressed). The shape of the molded body is not particularly limited and can be appropriately determined according to the application, but in this embodiment, a toroidal shape is used.

[0036] Next, the molded body is subjected to a final firing to obtain a sintered body (the ferrite composition of this embodiment). This final firing is performed to cause sintering, in which the powder particles in the molded body, which contain many voids, adhere to each other at a temperature below the melting point, thereby obtaining a dense sintered body. This final firing is preferably carried out at a temperature of 900 to 1300°C for about 2 to 5 hours. This final firing may be carried out in the atmosphere (air), or in an atmosphere with a higher oxygen partial pressure than the atmosphere.

[0037] The ferrite composition according to this embodiment is manufactured through the process described above.

[0038] Although embodiments of the present invention have been described above, the present invention is not limited in any way to these embodiments and can be implemented in various ways without departing from the spirit of the invention.

[0039] For example, in the embodiment described above, the toroidal shape is formed before the final firing, but it is also possible to form (process) the shape after the final firing.

[0040] Furthermore, in the embodiments described above, the ferrite composition according to this embodiment is used as a ferrite core, but it is not particularly limited and can also be suitably used as a ferrite portion of a magnetic head component, an inductor, a choke coil, or other coil component. In addition, the ferrite portion of a transformer component such as a power transformer for switching or inverter may be made with the ferrite composition of the present invention. Such electronic components can be suitably used in power supply devices and the like as a transformer, as one embodiment of the present invention. [Examples]

[0041] The present invention will be described below based on more detailed examples, but the present invention is not limited to these examples.

[0042] Example 1 First, Fe2O3, NiO, CuO, and ZnO were prepared as the main components. Bi2O3, SiO2, and CoO were prepared as the secondary components. The average particle size of the starting materials was 0.1 to 3 μm.

[0043] Next, the prepared main and secondary component powders were weighed and then wet-mixed in a ball mill for 5 hours to obtain the raw material mixture.

[0044] Next, the obtained raw material mixture was calcined in air at 900°C for 2 hours to obtain calcined material, and then wet-ground in a ball mill for 20 hours to obtain pulverized material.

[0045] Next, after drying the pulverized material, 1.0 part by weight of polyvinyl alcohol as a binder was added to 100 parts by weight of the pulverized material and granulated, and then sieved through a 20-mesh sieve to obtain granules. These granules were then pressure-molded at a pressure of 100 kPa to obtain a toroidal molded body (dimensions = outer diameter 18 mm × inner diameter 10 mm × height 5 mm).

[0046] Next, each of these molded bodies was fired in air at 1000-1250°C for 2 hours to obtain toroidal core samples as sintered bodies. The obtained samples were subjected to X-ray fluorescence analysis to measure the composition of the ferrite core. The results are shown in Tables 1 and 2. Furthermore, the following characteristics were evaluated for the samples.

[0047] (Permeability, DC superposition characteristics) For each toroidal core, copper wire was wound around it in 20 turns, and the permeability was measured using an LCR meter while applying a DC current from 0. The measurement conditions were a measurement frequency of 100 kHz, a measurement temperature of 23°C, and a measurement voltage of 0.5 mV. The permeability at a measurement level of 0.4 A / m was defined as the initial permeability μi, the permeability at an applied current of 2 A was defined as μi × Isat2A, and the permeability at an applied current of 3 A was defined as μi × Isat3A. From these values, the ratio of the permeability at an applied current of 2 A to the initial permeability was defined as Isat2A, and the ratio of the permeability at an applied current of 3 A to the initial permeability was defined as Isat3A, and these values ​​were calculated. The results are shown in Table 1.

[0048] A ratio of 25 or higher for μi×Isat2A was considered good, and a ratio of 24 or higher for μi×Isat3A was considered good. Furthermore, a ratio of 98% or higher for the permeability at 2 A / m relative to the initial permeability μi (Isat2A) was considered good, and a ratio of 94% or higher for the permeability at 3 A / m relative to the initial permeability μi (Isat3A) was considered good.

[0049] Examples 2-10, Comparative Examples 1-5 Except for changing the ratio of CoO, SiO2, or Bi2O3 as minor components to the proportions shown in Table 1, toroidal core samples were prepared in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0050] Examples 11-28, Comparative Examples 6-12 Except for changing the ratio of Fe2O3, NiO, CuO, or ZnO as the main components to the ratios shown in Table 2, and changing the ratio of CoO, SiO2, or Bi2O3 as the minor components to the ratios shown in Table 2, toroidal core samples were prepared in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The results are shown in Table 2. Figure 3 shows graphs illustrating the change in magnetic permeability with respect to the change in current for Example 1 and Comparative Example 12.

[0051] [Table 1]

[0052] [Table 2]

[0053] The results shown in Tables 1 and 2 indicate that the ferrite compositions according to each embodiment that satisfy the predetermined configuration yield ferrite cores with a superior balance between DC superposition characteristics and magnetic permeability compared to the comparative examples.

[0054] Furthermore, the results shown in Table 1 indicate that it is preferable to contain bismuth oxide in an amount of 0.15 to 0.45 parts by weight per 100 parts by weight of the main component (in terms of Bi2O3), and that it is preferable to contain silicon oxide in an amount of 2.5 to 3.1 parts by weight per 100 parts by weight of the main component (in terms of SiO2).

[0055] From the results shown in Table 2, it was found that it is preferable to contain 40.0 to 42.0 mol% of iron oxide (in terms of Fe2O3), 6.50 to 8.50 mol% of copper oxide (in terms of CuO), and 25.0 to 27.0 mol% of zinc oxide (in terms of ZnO). [Explanation of Symbols]

[0056] 2… Ferrite core

Claims

1. A ferrite composition having a main component and a secondary component, The aforementioned main component is, Iron oxide Fe 2 O 3 Converted to 39.0–43.0 mol%, Copper oxide in CuO equivalent amounts of 5.50 to 9.50 mol%, Zinc oxide in 24.0 to 28.0 mol% in terms of ZnO, The remainder contains nickel oxide, With respect to 100 parts by weight of the main component, the minor component is: Bismuth oxide 2 O 3 Converted to 0.05 to 0.50 parts by weight, Silicon oxide is SiO 2 Converted to 2.3 to 3.3 parts by weight, A ferrite composition containing cobalt oxide in an amount of 0.05 parts by weight or less (including 0) on a CoO basis.

2. A core having the ferrite composition described in claim 1.

3. An electronic component having the ferrite composition described in claim 1.

4. A power supply device having the ferrite composition described in claim 1.

Citation Information

Patent Citations

  • Sintered compact and coil component using the same

    JP2006027920A